-40-8m=-8(m+5)

Simple and best practice solution for -40-8m=-8(m+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -40-8m=-8(m+5) equation:


Simplifying
-40 + -8m = -8(m + 5)

Reorder the terms:
-40 + -8m = -8(5 + m)
-40 + -8m = (5 * -8 + m * -8)
-40 + -8m = (-40 + -8m)

Add '40' to each side of the equation.
-40 + 40 + -8m = -40 + 40 + -8m

Combine like terms: -40 + 40 = 0
0 + -8m = -40 + 40 + -8m
-8m = -40 + 40 + -8m

Combine like terms: -40 + 40 = 0
-8m = 0 + -8m
-8m = -8m

Add '8m' to each side of the equation.
-8m + 8m = -8m + 8m

Combine like terms: -8m + 8m = 0
0 = -8m + 8m

Combine like terms: -8m + 8m = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x*(3x-3)=2x*(x+6) | | 2x-9y=-8 | | (x+3)+x+x=130 | | (8x+8)(6x^2+6x+5)= | | 11/4x=4/3 | | (x+2)*(3x-6)=(x+1)*(3x-4) | | 2.3/x=5.2 | | x-(3x+4)=5-(4x+3) | | 10=3v-17 | | n-n=-4(2n-8)+8(n+12) | | 25=a(30-0)(30-60) | | x-56=64 | | -6+3(1-9v)=-24 | | x-32=28 | | 190+b=200b | | (x+5)*28=2x*21 | | 10x-22=8x+12 | | x*ln(x)=(ln(3))/3 | | (x+5)*28=2x+21 | | x^2+y^2-12x+4y=24 | | x+5*28=2x+21 | | s^2+20+4s= | | 4x=44p-16 | | 4m-30+m=3m+4 | | 3(-16+7x)-15x= | | 20*(20+x)=15*(15+3x) | | 6+17(-10-8g)= | | 2q-5=7q | | 75+2=15+5 | | 11-3x+6y=0 | | P(n)=3n | | 10a-7(-17a-13)= |

Equations solver categories